2004
DOI: 10.1177/154405910408300218
|View full text |Cite
|
Sign up to set email alerts
|

Dental Caries, Oral Hygiene, and Oral Clearance in Children with Craniofacial Disorders

Abstract: The reason that children with cleft palates tend to have a greater prevalence of tooth decay than normal children is unclear. We hypothesized that children with cleft palates would have increased oral clearance times for foods and, consequently, higher levels of caries and caries-associated micro-organisms than control children. Children aged 6-16 yrs, with (n = 81) or without (n = 61) cleft palates, were studied. Children with cleft palates had DMFT and dmft scores greater (p < 0.01) than those of the control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
147
0
15

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(165 citation statements)
references
References 24 publications
3
147
0
15
Order By: Relevance
“…Lauterstein and Mendelsohn [22], Lucas et al [24], and Hewson et al [16] did not observed significant difference in the caries prevalence of these two groups. But, other studies [1,4,6,14,18] found greater risk for individuals with CLP.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Lauterstein and Mendelsohn [22], Lucas et al [24], and Hewson et al [16] did not observed significant difference in the caries prevalence of these two groups. But, other studies [1,4,6,14,18] found greater risk for individuals with CLP.…”
Section: Discussionmentioning
confidence: 87%
“…The anterior teeth may have greater accumulation of plaque in individuals with cleft lip and palate, as they have lower lip elasticity due to the surgical repair, in addition to brushing fear in the cleft region [14]. Concerning to oral hygiene, may studies [1,25,30,32] reported worst results in individuals with cleft lip and palate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of factors can contribute to higher susceptibility such as enamel defects (Maciel, Costa et al 2005, Gomes, Neves et al 2009), early colonization of caries-associated microorganisms (Bokhout, van Loveren et al 1996) and impaired oral hygiene (Dahllöf, Ussisoo-Joandi et al 1989, Turner, Zagirova et al 1998, Wong and King 1998, Chopra, Lakhanpal et al 2014. A prolonged oral clearance time in children with CL/P may also contribute to a cariogenic environment (Ahluwalia, Brailsford et al 2004). Additionally, parents tend to overindulge children with CL/P and offer them sucrose-containing food and snacks as compensation for their medical condition (Johnsen 1984, Johnsen andDixon 1984).…”
Section: Dental Caries In Children With Cl/pmentioning
confidence: 99%
“…High and frequent consumption of sugar changes the balance between and presence of microorganisms in the oral biofilm (Fejerskov 1997, Moynihan and Petersen 2004, Zero 2004, Moynihan and Kelly 2014 increasing the amount and the proportion of acid producing bacteria such as mutans streptococci and lactobacilli (van Houte 1980, Loesche 1986). The magnitude of acid production is also depending on oral clearance time of fermentable carbohydrates depending on saliva secretion, orofacial sensibility and function (Ahluwalia, Brailsford et al 2004, Gabre, Norrman et al 2005, Dawes 2008). Furthermore, saliva buffering capacity will also affect duration of the acid demineralization of enamel and dentine (Lingström and Moynihan 2003).…”
Section: Etiology To Dental Cariesmentioning
confidence: 99%